Strategische Implikationen einer geringen Fertigungstiefe für die Automobilindustrie - Hans-Christian Krcal (University of Heidelberg, Department of Economics, 2007)
– In the German automobile industry the vertical integration, as an indicator of value added, is on average low. Beyond the argument of relative high labour costs for manufacturing, several specific reasons for the level of vertical integration, linked to the flexibility of business administration and the requirements of microeconomic mechanisms in the industry, can be found. The analysis based on empirical data including lessons from the early American automobile industry and theoretical explanations underlines the diversity of decision criteria towards a high or low level of vertical integration. The results facilitate the decision making of the OEM's on vertical integration.
Keywords: D23; L16; L62; M10; M11; 330; vertical integration; strategic management; automobile industry; Kfz-Industrie; Make-or- Buy-Entscheidung; Vertikale Integration; Strategisches Management; Betriebliche Wertschöpfung; Theorie; Deutschland